The Blue-Collar Brain - Van Orden, Guy; Hollis, Geoff; Wallot, Sebastian (Frontiers in Physiology, 2012)
Much effort has gone into elucidating control of the body by the brain, less so the role of the body in controlling the brain. This essay develops the idea that the brain does a great deal of work in the service of behavior that is controlled by the body, a blue collar role compared to the white collar control exercised by the body. The argument that supports a blue collar role for the brain is also consistent with recent discoveries clarifying the white collar role of synergies across the body's tensegrity structure, and the evidence of critical phenomena in brain and behavior.